Reducing Career Decision-Making Difficulties Through Rational Emotive Behavior Therapy-Based Career Counseling: A Single-Case Research - Annisa Putri Hidayati; Agung Nugraha; Dewang Sulistiana; Muhammad Muhajirin (Program Studi Bimbingan dan Konseling, 2026)
Career decision-making difficulty is a psychological barrier experienced by individuals, particularly adolescents, resulting from irrational beliefs and emotional distress that hinder the career exploration process. Research proves that these difficulties are often triggered by irrational thinking patterns and emotional pressures that impede career exploration. Individuals trapped in irrational mindsets tend to experience anxiety and procrastination in decision-making, which negatively impacts their readiness to enter the workforce or higher education.This study reports findings from research using a single-case A-B-A design to analyze the influence of Rational Emotive Behavior Therapy (REBT)-based career counseling in reducing career decision-making difficulties among adolescents. The participants consisted of two vocational high school (SMK) students (n=2) who exhibited high levels of career decision-making difficulty. The REBT-based counseling intervention was administered in six sessions, integrating cognitive restructuring techniques with the stages of career exploration. Self-report data were collected using the Career Decision-Making Difficulties Questionnaire (CDDQ) at pre-, during, and post-intervention time points.Visual analysis revealed that students participating in REBT-based career counseling experienced a significant decrease in career decision-making difficulties during the intervention and throughout the follow-up period. This evidence suggests the potential feasibility of using the REBT approach to help vocational students achieve independence and rationality in career planning.